STUDI EVALUASI TITIK KEMACETAN SIMPANG EMPAT DI JALAN KEBANGKITAN NASIONAL - JALAN BHAYANGKARA KOTA SURAKARTA - Alfian Restuyudha Adji Praditya (Jurnal Teknik Indonesia, 2020)
The city of Surakarta is a big city that has a function as a center for trade, tourism, culture, education, and sports which always experiences an increase in population and number of vehicles every year. The increasing number of facilities and infrastructure needs in the transportation sector must of course be balanced with the existence of supporters that make these transportation facilities more useful, namely the existence of roads and their management and performance of intersections. The intersection area with a signaling the National Awakening Road - Jalan Bayangkara is in a commercial area because there are many shops and settlements, so it has heavy traffic and a fast growth rate of traffic. This study aims to provide an overview of traffic congestion conditions that occur at the intersection of the four-lane National Awakening Street - Bhayangkara Street, Surakarta city and analyze the right solution to be applied in order to overcome congestion that occurs at the four-way intersection of Jalan Kebangkitan Nasional - Jalan Bhayangkara, Surakarta. From the results of existing calculations for the intersection without Signal Jl. National Awakening - Jl. Bhayangkara Kota Surakarta with the MKJI 1997 method, the value of the degree of saturation (DS) is obtained, namely = 1.12 or more than 0.85. So that we need several alternatives to describe congestion at the intersection. For the first alternative using the method of switching the road into one direction. The results of the degree of saturation (DS) = 0.32 for the Western approach, DS = 0.71 for the South approach. Then we also try to make a second alternative, which is to make the intersection a signaled intersection. So the value of the degree of saturation (DS) is = 0.47 for the north approach, DS = 0.73 for the south approach, DS = 0.63 for the eastern approach and DS = 0.73 for the western approach.Â Keywords: Intersection, intersection with signal, one direction, degree of saturationThe city of Surakarta is a big city that has a function as a center for trade, tourism, culture, education, and sports which always experiences an increase in population and number of vehicles every year. The increasing number of facilities and infrastructure needs in the transportation sector must of course be balanced with the existence of supporters that make these transportation facilities more useful, namely the existence of roads and their management and performance of intersections. The intersection area with a signaling the National Awakening Road - Jalan Bayangkara is in a commercial area because there are many shops and settlements, so it has heavy traffic and a fast growth rate of traffic. This study aims to provide an overview of traffic congestion conditions that occur at the intersection of the four-lane National Awakening Street - Bhayangkara Street, Surakarta city and analyze the right solution to be applied in order to overcome congestion that occurs at the four-way intersection of Jalan Kebangkitan Nasional - Jalan Bhayangkara, Surakarta. From the results of existing calculations for the intersection without Signal Jl. National Awakening - Jl. Bhayangkara Kota Surakarta with the MKJI 1997 method, the value of the degree of saturation (DS) is obtained, namely = 1.12 or more than 0.85. So that we need several alternatives to describe congestion at the intersection. For the first alternative using the method of switching the road into one direction. The results of the degree of saturation (DS) = 0.32 for the Western approach, DS = 0.71 for the South approach. Then we also try to make a second alternative, which is to make the intersection a signaled intersection. So the value of the degree of saturation (DS) is = 0.47 for the north approach, DS = 0.73 for the south approach, DS = 0.63 for the eastern approach and DS = 0.73 for the western approach.Â Keywords: Intersection, intersection with signal, one direction, degree of saturation